Divergent synthesis of prenylated carbazole alkaloid (+)-S-mahanimbine led to the discovery of a notch activator. Issue 86 (1st September 2016) - Yedukondalu, Nalli; Gupta, Gourav; R.Nadkarni, Janhavi; Gupta, Vivek Kumar; Syed, Sajad Hussain; Ali, Asif
Abstract : Mahanimbine a carbazole alkaloid transformed into (2–9 ) by POCl3 + DMF, further it screened against Notch pathway activation in which the compound8 exhibited an EC50 value of 0.85 μM. It also inhibited K562 HL cell proliferation and colony formation. Abstract : (+)-Mahanimbine (1 ), a prenylated carbazole alkaloid, was isolated from the stems of Murraya koenigii . Herein we developed a divergent synthesis by the Vilsmeier–Haack reaction, which involves unusual oxidative cyclization and transformation to several distinct tetracyclic carbazole natural products (2–9 ). The new chemical entities were identified by extensive 1D and 2D NMR data, HR-ESI-MS, and comparison with the known literature. Compounds2 and5 were further characterized by X-ray crystal analysis. Compounds (1–9 ) were screened against the notch pathway activation in which the new compound8 exhibited prominent notch activation in a reporter gene assay with an EC50 value equal to 0.85 μM. It also inhibited the cell proliferation and colony formation of the K562 human leukemia cell line.